Evaluation of Protein and Micronutrient Levels in Edible Cowpea (Vigna Unguiculata L. Walp.) Leaves and Seeds - Dakora, Felix D.; Belane, Alphonsus K. (Frontiers in Sustainable Food Systems, 2019)
Cowpea is the most important seed legume in Africa. Its leaves and seed are consumed to meet the dietary requirements of protein and micronutrient in rural African communities. In this study, leaf protein of 32 cowpea genotypes was 23-40% at Taung (South Africa), 28-40% at Wa and 24-35% at Manga (Ghana). Seed protein level was also up to 40% landrace Bengpla and more than 30% in nine other genotypes planted at Taung. Trace elements in cowpea leaves showed markedly high concentrations of Fe (2011 μg.g-1), Zn (150 μg.g-1) Mn (325 μg.g-1) and B (43 μg.g-1) in genotype Apagbaala, in contrast to the very low levels of Fe (273 μg.g-1), Zn (40 μg.g-1), Mn (219 μg.g-1) and B (32 μg.g-1) in genotype Encore. Leaf Fe concentration was highest in genotype Apagbaala (2011μg.g-1), followed by Fahari (2004 μg.g-1), Iron Grey (1302 μg.g-1), Line 2020 (944 μg.g-1), Bensogla (927 μg.g-1), Omondaw (605 μg.g-1), IT96D-1951(591 μg.g-1), IT93K-452-1 (574 μg.g-1), Ngonji (569 μg.g-1) and Mchanganyika (566 μg.g-1), and lowest in Bechuana white (268 μg.g-1). Cowpea seed also showed greater concentrations of Fe in genotype Soronko (67 μg.g-1), IT93K-452-1 (67 μg.g-1), Brown Eye (65 μg.g-1), Bensogla (61 μg.g-1) and TVU11424 (62 μg.g-1). Trace elements in cowpea seed differed among genotypes, and ranged from 45.1 to 67.0 μg.g-1 for Fe, 33.9 to 69.2 μg.g-1 for Zn, 10.1 to 17.4 μg.g-1 for Mn, 14.7 to 21.4 μg.g-1 for B, and 5.2 to 8.1 μg.g-1 for Cu. Genotypes Apagbaala, Fahari, Iron Grey and Line 2020 respectively exhibited 34.2-, 34.0-, 22.5- and 18.3-fold higher Fe concentration in leaves than seed, and 3.5-, 2,0-, 2,0-, and 3.5-fold greater Zn in leaves than seed (in that order). The genotypes that accumulated significantly high levels of protein and trace elements in cowpea leaves and seed, were generally high N2-fixers, thus suggesting a link between N2 fixation and cowpea’s ability to synthesize protein and accumulate nutrient elements in leaves and seed. Therefore, identifying cowpea genotypes that can enhance protein accumulation and micronutrient density in edible leaves and seed throμgh breeding has the potential to overcome protein-calorie malnutrition and trace element deficiency in rural Africa.